THE EFFECT OF TIKTOK PLATFORM TO DEVELOP STUDENTS' MOTIVATION IN SPEAKING ABILITY: A CLASSROOM ACTION RESEARCH - Ferstephanie, Jenni; Lady Pratiwi, Theodesia (Universitas Wiralodra, 2022)
This study was Classroom Action Research. It was conducted based on an internship of teaching practice in SMA Kristen Kalam Kudus Selatpanjang. It involved 25 students of grade 10 science class. The study aimed to identify the effectiveness of using Tiktok in improving students’ speaking skills. The research was organized step by steps such as planning, implementing, observation and reflection. The research instruments were observation, pre-test, and post-test. First, the students in the class were observed during learning English subjects, and then the pre-test and post-test were implemented to determine the students’ speaking skill improvement. The rubric was designed according to the aspect of speaking skills to assess the students’ skills. The results of the post-test showed that the students’ scores rapidly increased and were better than their pre-test. The average score for the pre-test was 2.51 points. After implementing TikTok in the test, the average score for the post-test was 4.65 points. Therefore, the implementation of TikTok proved it was effective to develop students’ speaking skills. In conclusion, the TikTok application engaged the students to enjoy the learning especially in improving their speaking skills. Students were free to express their ideas and creativity while making the content.